Peran Media Digital Dalam Meningkatkan Kemampuan Berpikir Kritis Melalui Pembelajaran Matematika (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
This study aims to examine the role of digital media in enhancing critical thinking skills through mathematics learning using a quantitative approach with the Systematic Literature Review method. The literature sources analyzed are derived from data indices such as Google Scholar, DOAJ, and Scopus, focusing on publications from 2020 to 2024. The findings indicate that digital media holds significant potential for creating interactive learning environments that can enhance critical thinking skills and deepen students' understanding of complex concepts, particularly in mathematics and science. However, several challenges need to be addressed, including the limitations of digital literacy among both teachers and students, as well as inadequate technological infrastructure. These challenges may hinder the effective implementation of digital media in educational contexts. This research is expected to provide insights into the importance of effective strategies for implementing digital media to improve the quality of education and foster the development of students' critical thinking skills